2005
DOI: 10.1097/01.aog.0000152303.80103.69
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gestational Age and Position on Peak Expiratory Flow Rate: A Longitudinal Study

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
4
11
1
Order By: Relevance
“…Inadequate nutrition due to morning sickness and altered eating habits may also result in muscular weakness, leading to decreased PEFR. Similar findings were reported by Singhal and Saxena [9] and Harirah et al [10] A descending trend in PEFR at different trimesters was observed by Chaitra and Maitri. [11] The decrease in the mean PEFR may be attributed to lesser force of contraction of expiratory muscles (i.e., anterior abdominal muscles) or to mechanical effect of enlarging gravid uterus, decreasing the vertical diameter by restricting the diaphragmatic movement.…”
Section: Discussionsupporting
confidence: 90%
“…Inadequate nutrition due to morning sickness and altered eating habits may also result in muscular weakness, leading to decreased PEFR. Similar findings were reported by Singhal and Saxena [9] and Harirah et al [10] A descending trend in PEFR at different trimesters was observed by Chaitra and Maitri. [11] The decrease in the mean PEFR may be attributed to lesser force of contraction of expiratory muscles (i.e., anterior abdominal muscles) or to mechanical effect of enlarging gravid uterus, decreasing the vertical diameter by restricting the diaphragmatic movement.…”
Section: Discussionsupporting
confidence: 90%
“…3,7,12 Other trials have a longitudinal design, some of which have non-pregnant women serving as controls, 2 and others in which an early postpartum value is taken as the non-pregnant reference. [4][5][6]8,10,11 Importantly, the chosen statistical methods and tests in previously published trials may have limited the ability to acknowledge significant changes in forced spirometry during pregnancy, because the correlation between measurements of the same subjects is not accounted for within the statistical method. The regression-based statistical methods with analysis of variance in repeated measures (mixed model) take into account the greater agreement between the data obtained from repeated measures of the same subject than measures from different subjects at the same time, providing new evidence for the natural development of various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found PEF to decline during pregnancy. 10,11 Using a portable flow meter Harirah et al 10 found PEF to decline with advancing gestational age. They explain their findings on a mechanical basis, pointing out the effect of the uterine enlargement and maternal weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These include: increase in tidal volume (30-40%), increase in inspiratory capacity (5-10%), increase in minute ventilation (30-50%), decrease in functional residual capacity (20%), decrease in expiratory reserve volume (20-30%), decrease in residual volume (20%), and a slight decrease in total lung capacity (5%), all of which may potentially affect airborne exposures. 7,15,[17][18][19] The increase in progesterone levels during pregnancy results in a decrease in intestinal tone and motility. 15 The decrease in intestinal motility leads to an increase in the absorption of nutrients such as calcium and iron, as well as other substances.…”
Section: Physiological and Behavioral Changes During Pregnancy And Lamentioning
confidence: 99%